2019
DOI: 10.1007/s13205-018-1545-z
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of I655V SNP of HER-2/neu in colorectal cancer: a study from India

Abstract: The present study was conducted to determine the prognostic significance of I655V SNP (rs1136201) is a genetic one in HER-2 oncoprotein in cases of colorectal cancer (CRC). We conducted a case-control study analysing 83 subjects (naïve primary CRC cases) who underwent CRC biopsy/colectomy and included 57 healthy control subjects. Analysis of HER-2 polymorphism was done by PCR-RFLP technique. The mean age was found to be 55.9 years; median age was 56 years and mode age was 54 years with a range of 43 (30-73). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…While in the overall analysis of our population, the genotypes of rs1136201 were not associated with colorectal cancers, we observed a protective association with the G allele conferring 1.8-fold lower risk of developing the disease relative to the A allele. Similar to our findings, the genotypic analysis of rs1136201 in the Indian as well as Scottish Caucasian population did not show a significant correlation with colorectal carcinoma [ 17 , 18 ]. Interestingly, when our population were segregated based on gender, the rs1136201 demonstrated that women carriers of the AG genotype and the G allele were at 3.6-fold (OR = 0.275, p =0.02093) and 4.1-fold (OR = 0.244, p =0.00705) lower risk of colorectal malignancy relative to the AA genotype and A allele, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…While in the overall analysis of our population, the genotypes of rs1136201 were not associated with colorectal cancers, we observed a protective association with the G allele conferring 1.8-fold lower risk of developing the disease relative to the A allele. Similar to our findings, the genotypic analysis of rs1136201 in the Indian as well as Scottish Caucasian population did not show a significant correlation with colorectal carcinoma [ 17 , 18 ]. Interestingly, when our population were segregated based on gender, the rs1136201 demonstrated that women carriers of the AG genotype and the G allele were at 3.6-fold (OR = 0.275, p =0.02093) and 4.1-fold (OR = 0.244, p =0.00705) lower risk of colorectal malignancy relative to the AA genotype and A allele, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Another meta-analysis study by Dahabreh and Murray also reported no association between HER2 Ile655Val polymorphism and breast cancer development which was based on 33 case-control studies including 20,461 cases and 23,832 controls [ 57 ]. Likewise, in a previous study from our group [ 58 ], we found no significant association of HER2 Ile655Val polymorphism with colorectal cancer in Indian population.…”
Section: Discussionsupporting
confidence: 57%